Recitation of Surah Yāsīn to Uncover Theft Cases at Dayah Insan Qur’ani Aceh - Bahri, Samsul; Yanda, Ullfa Meilly (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
Yāsīn is the name of one of the surahs of the Qur’an that is often recited by Muslims in various circumstances. In Dayah Insan Qur'ani, one of the religious education institutions in Aceh, the recitation was carried out when a theft occurred at Dayah. Surah Yāsīn recited for seven consecutive nights to reveal the theft perpetrator. Several questions about what the normative basis is, how it is recited, and how it affects; It needs to be answered through a study that combines literature review and field study. To obtain primary data, a series of observations, interviews and documentation studies were conducted. Data were analyzed using domain analysis techniques as commonly done in social research, as well as cultural theme analysis techniques that are often used in cultural research. The results showed that so far, no evidence has been found specifically regarding the teaching of the recitation of Surah Yāsīn to reveal theft cases. The recitation of Surah Yāsīn is performed jointly between the students and teachers for seven consecutive nights. This practice is seen as a form of tabarruk with verses of the Qur’an and is also part of tawassul. The influence felt by victims of theft includes a sense of calm and sincerity in accepting test of losing certain items. The effect of this activity on the perpetrators of theft is the emergence of fear, anxiety that encourages some of the perpetrators to return the stolen goods either secretly or openly.